Peran Kepala Sekolah dalam Membangun Budaya Sekolah sebagai Unggulan Sekolah di MI Muhammadiyah 1 Jombang - Khikmah Anjarrini; Ida Rindaningsih (MANAZHIM, 2022)
The principal plays an important role in an institution, including in building school culture. The existence of an effective school culture will have a positive impact on the formation of student character so that good habits emerge in the school that can be used as excellence in the school. This study aims to analyze the role and implications of the principal in building a school culture as a school excellence. The approach used is qualitative with the number of respondents 26 teachers, 123 students. data collection techniques using interviews, questionnaires, observation and documentation. The results of this study seen from the results of the percentage table of 93% indicate that the role of the principal of MI Muhammadiyah 1 Jombang in building a school culture as a superior school is by applying the primacy of the duties and functions of the principal as an educator, manager, administrator, supervisor, leader, innovator and motivator. well. And 80% of the implications of the principal in building a school culture as a superior school have a positive impact on student behavior. The findings are a framework chart of the principal's role based on existing theories and research results so that a school culture emerges. This success is juxtaposed with consistency and continuous effort so as to provide an effective school culture.